Construct of Transdisciplinary Curriculum Management in Global Ecotheology-Oriented Islamic Boarding Schools (Pesantren) - M. Nafiur Rofiq; Abd. Muis Thabrani; Erma Fatmawati; Devi Pramitha (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2026)
The epistemological dichotomy between religious knowledge (turāth) and modern science remains a fundamental obstacle for Islamic educational institutions in responding to the global climate crisis (planetary crisis). Pesantren are often trapped in “green” symbolism without comprehensive scientific integration. This study aims to reconstruct a transdisciplinary curriculum management model in pesantren with a global ecotheological perspective as an integrative solution. Employing library research with a qualitative–philosophical approach, this study analyzes authoritative literature related to Basarab Nicolescu’s theory of transdisciplinarity, Susan M. Drake’s integrative curriculum management, and the concept of Islamic ecotheology. The findings indicate that the construction of transdisciplinary curriculum management is built upon ecotheology as a core value that dissolves disciplinary boundaries. From a managerial perspective, this model requires: (1) a shift in curriculum design from subject-based to issue-based learning; (2) restructuring of organizational management through cross-disciplinary team teaching; (3) implementation of learning based on a living laboratory approach; and (4) authentic evaluation based on ecological behavior (eco-behavior). The implication of this construction is the emergence of a “Green Khalifah” graduate profile, possessing global scientific competence alongside strong spiritual roots as guardians of environmental sustainability.